Analysis of Financial Performance in Predicting Earning Growth - Eny Suprapti; Qonita Qonita; Ach. Syaiful Hidayat (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
This study aims to determine the effect of proxied financial performance with total asset turnover, current ratio, and return on assets in predicting earning growth in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2017. The research sample was 48 out of 144 manufacturing companies through purposive sampling technique. The technique of collecting data is secondary data. Data analysis uses descriptive statistics and multiple linear regression analysis. The hypothesis tests are using the t-test and F test. Based on the results of the study found that return on assets, the current ratio has an effect on earning growth while total asset turnover does not affect earning growth. Manufacturing companies should pay more attention to their financial performance related to CR and ROA. They must also increase their operational activities, and more optimally use the company's overall assets effectively. For further research, it is suggested that in predicting earning growth, there are many factors beside CR and ROA that will influence the earning growth.